Semiquantitative determination of chromium content of river bed soil of Buriganga river at different locations - Sadat, ME; Haider, A F M Yusuf; Abedin, KM; Wahadoszamen, M (© 2010 Journal of Bangladesh Academy of Sciences, 2017)
This article was published in the Journal of Bangladesh Academy of Sciences [© 2010 Journal of Bangladesh Academy of Sciences] and the definite version is available at: http://dx.doi.org/10.3329/jbas.v34i2.6856